Two sensor based H-infinity control of a piezoelectric tube scanner - Mahmood, Iskandar Al-Thani; Liu, Kexiu; Moheimani, S. O. Reza (2008)
The performance of a feedback-controlled piezoelectric tube scanner is limited by its inherent nonlinear properties such as hysteresis and creep, its mechanical resonance modes and its displacement sensor bandwidth and associated noise properties. Capacitive sensors have emerged as the displacement sensor of choice in piezoelectric tube scanners. Resolution of a capacitive sensor is largely determined by its bandwidth and noise density which is typically in the order of 20 pm/root Hz for a +/-100 micrometer range. Consequently, to achieve sub-nanometer resolution, the sensors bandwidth needs to be made small. Achieving satisfactory tracking performance using a low-bandwidth displacement sensor is a challenging task. To improve the bandwidth, the piezoelectric strain voltage induced in the electrode opposite to the actuating electrode is used as a secondary measurement. A two-sensor-based H-infinity controller is designed and implemented on a prototype piezoelectric tube nanopositioning system. The tube is driven by a charge amplifier to reduce the hysteresis. Experimental results demonstrate a significant increase in the tracking bandwidth due to the use of the additional sensor.